Design and analysis of multiphase dc/dc boost converter with minimized input current ripple - Abdul Gani, Ahmad Faiz Hilmi (2021)
Nowadays, the DC source has become alternatives options to solve global warming and energy consumption. DC/DC converter is widely used in many low voltage application such as telecommunication, electric vehicle, aircraft, etc. which range between 12V until 48V. Besides, the DC/DC converter also can be applied in home applications; television, radio, washing machine, CCTV and so on. DC/DC boost converter is used to step up the input voltage into the desired voltage. To increase the conventional boost converter capability, the multiphase structure with interleaved technique is proposed. This design capable to reduce current stress, input current ripple and conduction losses. Moreover, the input current ripple only can be alleviated by using a suitable duty cycle. Therefore, the Modified Pulse Width Modulation (MPWM) is applied to reduce the input current ripple in wide ranges. Besides, the Zero-Voltage Switching (ZVS) technique is used to reduce the switching losses across the switch. The proposed converter is simulated by using OrCAD Pspice software programs. The PWM switching scheme is designed using Quartus II software before it uploaded into Altera DE2-70 device. A hardware prototypes with 15 V to 30 V input voltage,30 V to 60V output voltage, 50W to 200W output power and 100 kHz switching frequency is built and tested to demonstrate the effectiveness of the proposed converter. The 3-level multiphase boost converter with ZVS technique achieves 91.95% efficiency compared to hard-switching multiphase boost converter. Despite that, the switching loss is completely reduced by using ZVS technique in certain power ranges. Additionally, the input current ripple also can be reduced by using a modified PWM switching signal compared common interleaved technique in wide duty ranges.